2013
DOI: 10.1088/1748-9326/8/3/035033
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation response to extreme climate events on the Mongolian Plateau from 2000 to 2010

Abstract: Climate change has led to more frequent extreme winters (aka, dzud) and summer droughts on the Mongolian Plateau during the last decade. Among these events, the 2000-2002 combined summer drought-dzud and 2010 dzud were the most severe on vegetation. We examined the vegetation response to these extremes through the past decade across the Mongolian Plateau as compared to decadal means. We first assessed the severity and extent of drought using the Tropical Rainfall Measuring Mission (TRMM) precipitation data and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 61 publications
3
73
0
1
Order By: Relevance
“…The significant decrease trend of Agbtc in EA after 1994 could not be explained by precipitation as their correlations were not significant (Table 1 and Figure S6). Although the negative correlation between the Agbtc and temperature was not significant, the significant increased temperature may suppress grassland biomass through influencing water availability [42,44].…”
Section: Controlling Factors Of Biomass Carbon Changementioning
confidence: 94%
“…The significant decrease trend of Agbtc in EA after 1994 could not be explained by precipitation as their correlations were not significant (Table 1 and Figure S6). Although the negative correlation between the Agbtc and temperature was not significant, the significant increased temperature may suppress grassland biomass through influencing water availability [42,44].…”
Section: Controlling Factors Of Biomass Carbon Changementioning
confidence: 94%
“…Actually, the impacts of climate changes on vegetation growth are diverse and not constant. Numerous studies have validated the responses of NDVI to climatic changes, and concluded that they differed among vegetation types (Breda et al 2006;John et al 2013). For example, Li and Tao (2000) demonstrated that correlation between annual NDVI and annual precipitation stronger over grasslands than over areas covered with shrubs and forests.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effects of extreme droughts on vegetation have been widely studied using remote sensing data or drought indices [22][23][24][25][26][27][28][29]. The relationship between vegetation indices and drought indices, such as SPI [23] or PDSI [30], was found in different land cover or different seasons.…”
Section: Introductionmentioning
confidence: 99%